2021
DOI: 10.1177/15579883211001197
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Psychosocial Resources Mediate Racial/Ethnic Differences in Psychological Health Among Gay and Bisexual Men: A Longitudinal Analysis Using Structural Equation Modeling

Abstract: A large body of research demonstrates disparities in psychological health attributed to sexual minority identity, racial/ethnic minority identity, and socioeconomic status (SES). Fewer studies have explicated the role of these multiple attributes on psychological health and explored the role of SES and psychosocial resources in determining outcomes. We analyzed data from Project STRIDE, a longitudinal survey involving a diverse sample of gay and bisexual adult men ( n = 198). Using structural equation modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
1
2
0
1
Order By: Relevance
“…The intersectional analysis of potential factors related to the mental health of minority groups reiterates the importance of the socioeconomic situation for the individual wellbeing; furthermore, clinical frameworks related to mental health, such as drug abuse, may be related to social stress. These data corroborate the findings of this study, which shows that participants had certain level of financial dependence/ instability, high levels of drug abuse, and intense fluctuations in their responses about social support, with a tendency of social satisfaction from low to medium (12) .…”
Section: Discussionsupporting
confidence: 91%
“…The intersectional analysis of potential factors related to the mental health of minority groups reiterates the importance of the socioeconomic situation for the individual wellbeing; furthermore, clinical frameworks related to mental health, such as drug abuse, may be related to social stress. These data corroborate the findings of this study, which shows that participants had certain level of financial dependence/ instability, high levels of drug abuse, and intense fluctuations in their responses about social support, with a tendency of social satisfaction from low to medium (12) .…”
Section: Discussionsupporting
confidence: 91%
“…CON3: I often disagree with AI in the experiment CON4: In my team, conflicts about ideas are frequent CON5: The degree of disagreement between me and AI in the team Dependence behaviors (DEP) Prompt: "Please indicate your agreement with the following statements about you:" Scaling: five-point Likert-type scale anchored on 1 5 strongly disagree, 2 5 disagree somewhat, 3 5 neither agree/disagree, 4 5 agree somewhat and 5 5 strongly agree above the required value of 0.5 (Chin, 1998). These results suggested that our measurement model had adequate convergent validity (English et al, 2020;Jaspal et al, 2020;Lu et al, 2021;Masa et al, 2021). Therefore, this research questionnaire had high consistency and stability regardless of the single construct or the whole that showed that the reliability of the questionnaire was satisfactory.…”
Section: Intellectual Ability Of Ai (Int)mentioning
confidence: 62%
“…Análise interseccional de possíveis fatores relacionados à saúde mental de grupos minoritários ratifica a importância da situação socioeconômica para o bem-estar individual; ademais, quadros clínicos relacionados a saúde mental, como o uso abusivo de drogas, podem estar relacionados ao estresse social. Esses dados corroboram o encontrado no presente estudo, onde os participantes apresentaram-se com certo grau de instabilidade/dependência financeira, alto índice de consumo de drogas e intensa flutuação nas respostas sobre o suporte social, apresentando uma tendência de baixa à média satisfação social (12) .…”
Section: Discussionunclassified